Optimizing Radial Distribution Network Performance Through Microgrid Integration Using a Hybrid PSO-HSA Algorithm - Demsew Mitiku Teferra; Livingstone M. H. Ngoo; George N. Nyakoe (Journal of Electrical and Computer Engineering)
The development of microgrids has emerged as a strategic solution to address the challenges inherent in radial distribution networks (RDNs). By integrating a microgrid system on the low-voltage side of the distribution feeders, it enhances the flexibility, reliability, and efficiency of power delivery to customers. Radial power distribution systems, characterized by long feeders and time-varying, nonlinear loads, are primary sources of inefficiency, poor power quality, and stability issues within the distribution network. The microgrid is integrated into the RDN, and its impact is assessed using a hybrid of particle swarm optimization and harmony search algorithms (Hybrid PSO-HSA). The proposed hybrid PSO-HSA algorithm leverages the strengths of both particle swarm optimization (PSO) and harmony search algorithm (HSA) to address these challenges. PSO contributes to rapid convergence and global search capabilities, while HSA enhances local search efficiency and solution diversity. The combination of these algorithms aims to minimize power losses, improve voltage profiles, and enhance overall network stability. This study examines the microgrid’s impact on the distribution system both before and after the injection of additional load, using simulations on three radial distribution test systems (IEEE_15, 33, and 69). The performance of the radial distribution system is significantly improved by the microgrid when optimized using the hybrid PSO-HSA algorithm. For the IEEE_15-bus radial distribution system, for example, the VSI improves to 0.932, 0.919, and 0.936, while the AVDI is minimized to 0.00016, 0.00022, and 0.00013 using the PSO, HSA, and hybrid PSO-HSA algorithms, respectively. The system’s efficiency also improves by 69.2%, 65.2%, and 69.8%, respectively. In addition, the voltage profiles of the IEEE_15, 33, and 69 bus systems are improved by 2.099%, 3.995%, and 2.185%, respectively, when the hybrid PSO-HSA algorithm is applied.